MEDIA INTERAKTIF PEMBELAJARAN INTERAKTIF MATA PELAJARAN BIOLOGI UNTUK SEKOLAH MENENGAH ATAS (Studi Kasus : SMA Negeri 10 Batanghari Kelas XI IPA) - Ezrifal Sany (JURNAL AKADEMIKA)
Senior high schools 10 Batanghari located in the district of Muaro Bulian Jambi province is in needof quality improvement and the ability of each student in understanding the subject matter, his special subjects of Biology at the material that is Kingdom Animalia Vertebrate animals (vertebrate) and invertebrates (invertebrates), for class XI Science by using face-to- face class. Submission of material is usually just use the lecture method as well as the lack of motivation of students in the learning process can impede the progress of State high schools 10 Batanghari scientific achievement in improving its students. Making multimedia -based applications aim to build a Teaching Tool application that can assist teachers in presenting the material and to increase students' understanding of Vertebrate animals (vertebrate) and invertebrates (invertebra te). The expected outcome of this Teaching Tool is an application of the growing interest of learning the students to learn the material Vertebrate Animals (vertebrate) and invertebrates (invertebrate), and in order to facilitate teachers in the delivery of this material so that the learning process is more optimal duration Watu very limited, as well as to improve the quality of learning of high school students 10 Batanghari, particularly for students of class XI Science.